Syngas Production Through Non Catalytic Gasification of Empty Fruit Bunch and Catalytics Using Natural Bentonite - Rahayu, Atika; Faizal, Muhammad; Bahrin, David (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2024)
The high increase in production of empty oil palm fruit bunch waste in the palm oil industry has not been utilized optimally. Empty Fruit Bunch (EFB) must be further processed with the aim of reducing pollution and increasing use value. The aim of this research is to compare syngas products using TKKS waste and using natural bentonite catalysts. Gasification is carried out at temperatures of 450, 500, 550, and 600°C. The addition of a natural bentonite catalyst to the gasification process can increase the composition and volume of the gas. In the gasification process, the higher the reaction temperature, the greater the conversion percentage produced. This is proven in the syngas product produced at a temperature of 600 °C. In non-catalytic EFB gasification, the largest concentrations of H2 and CO were obtained, namely 21.86%vol and 11.93%vol. With the addition of natural bentonite, the concentrations of H2 and CO increased by 27.18%vol and 14.21%vol. Gasification efficiency is seen from the optimum H2/CO ratio value of 1.91, CG/NCG value of 5.81, CCE value of 77.07, and CGE value of 62.67. The calorific value in terms of the optimum HHV and LHV values ​​is 11.40 MJ/Nm3 and 10.26 MJ/Nm3 using a bentonite catalyst. EFB catalytic gasification using a natural bentonite catalyst is better for producing high-quality synthetic gas products for the production of good environmental fuel.